Evaluasi Pengelolaan Parkir Tepi Jalan Umum Kota Semarang (Tahun 2016-2019) - Irfan - Fajri; Dzunuwanus Ghulam Manar (Journal of Politic and Government Studies, 2020)
The background of the writing of this thesis is from the author who previously had a course on Labor Politics and discussed parking attendants in the City of Semarang. Then after conducting several surveys and observations, it was found that there were still many shortcomings, problems and obstacles in parking management in the City of Semarang itself. This results in reduced parking fees and automatically reduces the Regional Budget (PAD) revenue that the Semarang City Government receives annually. In this study the authors used qualitative research methods, namely by conducting interviews with several sources and informants that the author needed in achieving the research results that the authors wanted, as well as through surveys, observations, and documentation. This study uses a literature review of policy formulation and stakeholder analysis. The resource persons in this study were the Head of the Parking Collection Section at the Semarang City Transportation Service, the Head of the Parking Arrangement and Licensing Section for the Semarang City Transportation Service, the Head of the Sub-Division of Extension and Regional Revenue Services, and the Head of the Sub-Division for Administration of Levies in the Non-Tax Regional Revenue, Bapenda. , Semarang city. Based on the results of the research and discussion that has been carried out, it was found that in the process of determining parking fee targets in Semarang City, it involved many stakeholders including the Semarang City DPRD, Semarang City Transportation Service, Regional Financial and Asset Management Team, Regional Government Budget Team, and also the Transportation Service as the manager of the parking sector in the city of Semarang. Furthermore, the authors also found that local government revenue through parking sector levies was not maximized as a whole. How does the parking fee target managed by the Semarang City Transportation Agency never reach the target that has been set every year. Some of the problems found were the discovery of illegal parking lots, the absence of parking tickets, parking attendants who did not make deposits, to the existence of other stakeholders involved in the process of collecting the parking fees. For this reason, a solution is needed in the management of public roadside parking, which is to be more assertive and disciplined from the Transportation service to naughty parking attendants and to impose penalties on illegal parking attendants through socialization with several stakeholders such as Pol PP, Banser and the Police, as well as more optimization in the management of parking KTA by parking attendants so that they are valid and recognized by the Semarang City Transportation Agency and are no longer classified as illegal parking.